ONLINE LEARNING AND FACE-TO-FACE LEARNING: STUDENTS’ PREFERENCES AND PERCEPTIONS - Norhasanah (TEFLA Journal (Teaching English as Foreign Language and Applied Linguistics Journal), 2021)
The Covid-19 pandemic has shifted face-to-face learning into online learning. This learning system has been conducted for more than a year. Teachers and students have to adapt to this condition. With such experience, students must have their opinions on these two learning modes. This study is aimed to find out students’ preferences and perceptions toward online learning that has been carried out during the pandemic and face-to-face learning that many educational institutions usually offer. It is also tried to investigate whether their perceptions influence their preferences for the learning mode. The data was collected using a survey and then analyzed using SPSS Statistics. Pearson Product Moment was used to analyze the correlation between variables, while students’ preferences and perceptions were explained through descriptive statistics. The results showed that 83 percent of students preferred face-to-face learning; they gave more positive responses toward face-to-face learning even though they also admitted the advantages offered by online learning. Another finding indicated that flexibility, ease of course, convenience, and time-saving influence students’ preference for online learning, while interaction and learning experience became some reasons for students to choose face-to-face learning. Most of the students had internet access to take online classes. However, they still considered face-to-face learning as an ideal class because 87 percent of students agreed that not all regions in Indonesia had good internet access to conduct online learning. This study was limited in generalizability since it was conducted in one university with only 64 students as participants; it was a small number of populations. However, this research could provide a little description and information related to students’ opinions on online learning. This study still needs to be improved with more participants and conducted in other places and situations.